Lessons Learnt From Communal Waste Water Treatment Plant (WWTP) At Kampung Polehan, Malang City - Amalia, Resmi (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018DO - 10.18860/icgt.v9i1.851, 2019)
Kampung Polehan is appointed as one of slums in Malang City. This is inseparable from the problems of sanitation services faced. To overcome sanitation problems, Kampung Polehan, especially RW 1, has received assistance in the construction of WWTP. However, this still causes environmental problems, especially related to its operations and maintenance. Therefore the purpose of this study is to describe the performance of WWTP management in Kampung Polehan, especially its operations and maintenance. The method is descriptive using a case study approach. Problems related to WWTP in the study area tend to be due to lack of maintenance carried out by users and managers.